Outcomes of MYC‐associated lymphomas after R‐CHOP with and without consolidative autologous stem cell transplant: subset analysis of randomized trial intergroup SWOG S9704. (13th April 2016) - Puvvada, Soham D.; Stiff, Patrick J.; Leblanc, Michael; Cook, James R.; Couban, Stephen; Leonard, John P.; Kahl, Brad; Marcellus, Deborah; Shea, Thomas C.; Winter, Jane N.; Li, Hongli; Rimsza, Lisa M.; et al.
Summary: Double hit lymphoma (DHL) and double protein‐expressing (MYC, BCL2) lymphomas (DPL) fare poorly with R‐CHOP (rituximab + cyclophosphamide, doxorubicin, vincristine, prednisolone); consolidative autologous stem cell transplant (ASCT) may improve outcomes. S9704, a phase III randomized study of CHOP +/−R with or without ASCT enabled evaluation of intensive consolidation. Immunohistochemistry (IHC) identified 27 of 198 patients (13·6%) with MYC overexpression; 20 (74%) harboured concurrent BCL2 overexpression. Four had DHL and 16 had DPL only. With median 127 months follow‐up, there is a trend favouring outcomes after ASCT in DPL and MYC protein overexpressing patients, whereas all DHL patients have died irrespective of ASCT.